Analisis Kebutuhan Pengembangan Model Problem Base Learning (PBL) Berbasis Kontekstual untuk Meningkatkan Kemampuan Siswa dalam Menganalisis Konsep - Siti Endang Apriyanti; Andi Mariono; Andi Kristanto; Khusnul Khotimah (Universitas Cokroaminoto Palopo, 2024)
The urgency or main issue in this study lies in the low problem-solving skills of students, particularly in understanding and solving story problems based on real-life contexts in algebra learning. This study aims to analyze the needs and impact of the contextual Problem-Based Learning (PBL) model on students' ability to analyze mathematical problem concepts. This research is a descriptive qualitative study, designed to deeply explore students' experiences, perceptions, and abilities in addressing mathematical problems through the PBL approach. This study employs survey and quasi-experimental methods to measure the impact of the application of this learning model, as well as to identify factors influencing its success in the context of mathematics education. The study was conducted at the Sekolah Indonesia Kuala Lumpur over one semester of learning, involving 88 seventh-grade students as the research subjects. The selection of subjects was purposive, choosing students who participated in mathematics learning with the contextual PBL approach, with the aim of exploring the needs and impact of applying this learning model. The main instruments used to collect data in this study were observation, essay tests, and questionnaires. Analysis was carried out using descriptive qualitative methods. The results of the study showed that the application of the contextual Problem-Based Learning (PBL) model played a significant role in improving students' ability to analyze mathematical concepts, particularly in algebra learning. Contextual PBL allows students to connect abstract mathematical concepts with real-life situations, which strengthens their conceptual understanding and encourages their active involvement in solving problems. This approach not only improves students' academic understanding but also develops critical thinking and problem-solving skills useful in everyday life. Therefore, the application of contextual PBL should be expanded, as it supports meaningful learning and prepares students to face complex challenges.